KOMUNIKASI DAN MEDIA ANTARBUDAYA: FORMULASI KOMUNIKASI ANTARBUDAYA DALAM PERKEMBANGAN INFORMASI TEKNOLOGI - Ainiyah (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2015)
In the information era, everything went self the self cheap, fast, right, and accurate. Communication technologies date created what is called ‘public dunia’. The development of communication technologies be inseparable in human life. Plus the development of internet, communication medias being closely in connection with human. Man was easier associated with each other. Social media being evolved to answer the need and lead to change processes of communication between humans. No exception cross-cultural communication also enter new era. Cross Cultual Communication progressed with the advent of the communication technologies. Internet media connecting different persons culture, dif-ferent language, identity, view of life material religion, can do communication easily. The emergence of the internet and cyber communication to be the Cross Cultual medium in communication, so it could not be rejected in Cross Cultual communication application create a new namely intercultural cybercommunity.